If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -2x + -3x = -12 Combine like terms: -2x + -3x = -5x 3 + -5x = -12 Solving 3 + -5x = -12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -5x = -12 + -3 Combine like terms: 3 + -3 = 0 0 + -5x = -12 + -3 -5x = -12 + -3 Combine like terms: -12 + -3 = -15 -5x = -15 Divide each side by '-5'. x = 3 Simplifying x = 3
| 18/5/8= | | 4x-x=20+2+3 | | .2a=.5 | | 2+x=16 | | 5x-20+3x+8=180 | | 18*5/8= | | 2x-1=23 | | f=1.8(22)+32 | | 1500+594.25n=22893 | | -2d+2=-4(d-2) | | 9-y+6y=1 | | x+50+f=180 | | 2y=-x+2 | | 330+25n=455 | | n-7=-23 | | x-(-41)=-26 | | 4a^2-2a=0 | | 9n+324=648 | | -7-6x=5x+3-x | | x^2+16x+60= | | x+5y=42 | | 24=m+6 | | 40-3n=023 | | 3-8a=-12-3a | | x-9=-29 | | 25000(4+3x)=125000 | | 205+4n=289 | | x+6=-18 | | 3x+8+5x+4y+5x-20=180 | | x+6=-29 | | -2x+4y=70 | | 4-3(2x+1)=7 |